META-ANALYSIS OF COMPUTER-BASED MATHEMATICS LEARNING IN THE LAST DECADE SCOPUS DATABASE: TRENDS AND IMPLICATIONS - Maximus Tamur; Sabina Ndiung; Tommy Tanu Wijaya; Emilianus Jehadus; Eliterius Sennen; Robert Weinhandl (Jurnal Infinity, 2023)
Computer-Based Mathematics Learning (CBML) has gone global in the last decade and is making a substantial impact for educational purposes. But the fact is that in the scientific literature, it is found that studies aimed at testing these theoretical assumptions have inconsistent results. In this regard, this meta-analysis was conducted to determine the effect of CBML and to analyze categorical variables to consider the implications. Data were retrieved from the Scopus database using Publish or Perish between 2010 and 2023. This study examined 29 independent samples from 28 eligible primary studies with 1179 subjects. The population estimate was based on a random effects model, and the CMA software was used as a calculation aid. The study's results provide an overall effect size of 1.03 (large effect). This indicates that applying CBML significantly affects students' mathematical abilities. The four categorical variables considered in the study are discussed to clarify research trends. Furthermore, the research implications are outlined and contribute to future CBML implementation arrangements.